Using COVID-19 as a vehicle for enabling geographical thinking in teacher education (The Journal of Geography Education in Africa, 2023)
This article describes a curriculum innovation conceptualized in the March/April 2020 COVID-19 lockdown and implemented over a six-month period (April to September 2020). Written from a position of hindsight, the article responds to the question: How can the geography of the COVID-19 pandemic enable teachers’ geographical thinking? More specifically, it addresses the need for practical ‘how to’ examples of responsive geography education curriculum making processes and pedagogical approaches employed in teacher education in the context of the COVID-19 pandemic. The article begins by describing how, despite the many challenges faced across education sectors, COVID-19 was able to be used as a ‘teachable moment’ in the geography module of the Understanding the Social and Physical World course offered in the Bachelor of Education (Foundation Phase Teaching) qualification at a South African university. The article describes the curriculum design and conceptual framing, revealing how the constructivist epistemology used was employed to elicit, build on, and expand the students’ knowledge of the pandemic from a geographical perspective.  This article critically reflects on how I used COVID-19 content to conceptualize and implement a curriculum that was responsive to the context in which we found ourselves while maintaining disciplinary integrity. In showcasing select examples of how this was achieved, the paper offers insights on the lessons learned which may stimulate curriculum innovation and pedagogical responsiveness in other geography teacher education programmes.
Keywords: curriculum innovation; constructivist epistemology; geographical thinking; active learning; teacher education; COVID-19 pandemic